2013
DOI: 10.1084/jem.20131199
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar macrophages develop from fetal monocytes that differentiate into long-lived cells in the first week of life via GM-CSF

Abstract: Alveolar macrophages differentiate from fetal monocytes in a GM-CSF–dependent fashion and colonize the alveolar space within a few days after birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

67
1,106
7
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,017 publications
(1,207 citation statements)
references
References 59 publications
67
1,106
7
2
Order By: Relevance
“…The lack of effect on other M1/M2 markers is perhaps a reflection of the lack of well-defined markers to unambiguously define the human macrophage activation state (47). It could also be explained by the different methods used for achieving monocyte differentiation and macrophage stimulation; in our studies, we used GM-CSF as a differentiation factor to model AMs (48,49). GM-CSF also promotes an M1-like phenotype, more closely mimicking activated AMs that would be present in the alveoli of patients with ARDS.…”
Section: Msc-derived Ev-treated Murine Amsmentioning
confidence: 90%
“…The lack of effect on other M1/M2 markers is perhaps a reflection of the lack of well-defined markers to unambiguously define the human macrophage activation state (47). It could also be explained by the different methods used for achieving monocyte differentiation and macrophage stimulation; in our studies, we used GM-CSF as a differentiation factor to model AMs (48,49). GM-CSF also promotes an M1-like phenotype, more closely mimicking activated AMs that would be present in the alveoli of patients with ARDS.…”
Section: Msc-derived Ev-treated Murine Amsmentioning
confidence: 90%
“…This alveolar phase of lung growth lasts until 3 years of age and is controlled by many growth factors and cytokines that could also influence (Schittny et al, 2008). Fetal lung is first populated around E12 by CD45 + yolk sac-derived macrophages (De Kleer et al, 2014;Guilliams et al, 2013;Schulz et al, 2012;van de Laar et al, 2016). We recently have shown that this first wave of yolk sac-derived macrophages is followed by a consecutive wave of fetal liver-derived monocytes that enter the lung around E18, the start of the saccular phase in mice, and give rise to alveolar macrophages (AM) under the influence of GM-CSF van de Laar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A unified nomenclature has recently been proposed to attempt to circumvent this fundamental problem in which MPS cells can be classified primarily by their ontogeny and secondarily by their location, function, and phenotype in the steady-state and in inflammatory conditions (13). Even though a number of articles using sophisticated in vivo technology in mice have recently appeared addressing the origins of tissue macrophages during development, there is still debate around the fundamental question of the contribution, if any, of blood monocytes, including their subpopulations, to tissue macrophages in the adult at steady-state, and also to what extent local macrophage proliferation contributes to their homeostatic control or to that during inflammatory reactions (3,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%